Volume 4B: Pipeline and Riser Technology 2013
DOI: 10.1115/omae2013-10891
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Riser Response Induced by Combined Slug Flow and Wave Loads

Abstract: Flexible risers provide optimum solutions for deep water offshore fields. Reliable dynamic analysis of this kind of slender structure is crucial to ensure safety against long time fatigue failure. Beyond the effects from wave loads, the influence from transient internal slug flow on the slender structure dynamics should also be taken into account. In this study two coupled in-house codes were used in order to identify and quantify the effects of an internal slug flow and wave loads on the flexib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Ortega et al (2012) reported a computational method to analyze the interaction between an internal slug flow and the dynamic response of flexible risers. Extending previous work, Ortega et al (2013) studied the interaction between an internal slug flow plus an external regular wave and the dynamic response of a flexible riser.…”
Section: Introductionmentioning
confidence: 98%
“…Ortega et al (2012) reported a computational method to analyze the interaction between an internal slug flow and the dynamic response of flexible risers. Extending previous work, Ortega et al (2013) studied the interaction between an internal slug flow plus an external regular wave and the dynamic response of a flexible riser.…”
Section: Introductionmentioning
confidence: 98%